Eeyarestatin I derivatives with improved aqueous solubility. Issue 21 (1st November 2016) - Ding, Rui; Zhang, Ting; Xie, Jiashu; Williams, Jessica; Ye, Yihong; Chen, Liqiang
Graphical abstract: Abstract: Inhibition of p97 (also known as valosin-containing protein (VCP)), has been validated as a promising strategy for cancer therapy. Eeyarestatin I (EerI) blocks p97 through a novel mechanism of action and has favorable anti-cancer activities against cultured cancer cells. However, its poor aqueous solubility severely limits its in vivo applications. To circumvent this problem, we have identified EerI derivatives that possess improved aqueous solubility by introducing a single solubilizing group. These modified compounds preserved endoplasmic reticulum (ER) stress-inducing and antiproliferative activities as well as generally good in vitro metabolic properties, suggesting that these EerI derivatives could serve as candidates for further optimization.